2005
DOI: 10.1111/j.1399-3054.2005.00561.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide generation upon growth of Antarctic Chlorella sp. cells

Abstract: The aim of this work was to characterize nitric oxide (NO) generation during the growth of Chlorella sp. cells. The profile of NO production was compared with that observed in Chlorella from temperate climate and Antarctic Chlamydomonas sp. A distinctive electron paramagnetic resonance (EPR) signal for the adduct MGD-Fe-NO was detected in the Antarctic Chlorella sp. cells on days 6 and 7 of growth. An assay based upon the time-dependent detection of NO by EPR was developed to assess both nitrate reductase (NR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 38 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…In fact, when production of NO was inhibited by the NOS inhibitor NMMA, growth was inhibited, implying that NO may play a protective role in Seminavis. Inhibition of growth by addition of NOS inhibitors was also seen in sea urchin embryos and in Antarctic Chlorella and Chlamydomonas (Estevez and Puntarulo 2005). Although addition of the inactive optical isomer of the NOS inhibitor to sea urchin embryos resulted in some inhibition of growth, it was not to the extent seen with the active isomer, and hence the inhibitory effect on morphogenesis was attributed to a suppression of NO production (Semenova and Ozernyuk 2004).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In fact, when production of NO was inhibited by the NOS inhibitor NMMA, growth was inhibited, implying that NO may play a protective role in Seminavis. Inhibition of growth by addition of NOS inhibitors was also seen in sea urchin embryos and in Antarctic Chlorella and Chlamydomonas (Estevez and Puntarulo 2005). Although addition of the inactive optical isomer of the NOS inhibitor to sea urchin embryos resulted in some inhibition of growth, it was not to the extent seen with the active isomer, and hence the inhibitory effect on morphogenesis was attributed to a suppression of NO production (Semenova and Ozernyuk 2004).…”
Section: Discussionmentioning
confidence: 96%
“…In algae, research into NO signaling is in its infancy. General production of NO in algae, such as Chlamydomonas (Sakihama et al 2002), Antarctic Chlorella (Estevez and Puntarulo 2005), Dasycladus (Ross et al 2006), Scenedesmus (Mallick et al 2002), dinoflagellates (Zhang et al 2006), and in the diatom Skeletonema (Zhang et al 2006) has been shown. In the chlorophyte alga Dascycladus vermicularis , NO is produced as a result of wounding, leading to a healing response (Ross et al 2006).…”
mentioning
confidence: 99%
“…[27]. Few other studies reported the presence of little amounts of NO, in the order of 10 -8 -10 -9 mol/l, in the culture medium of several marine microalgae, such as H. akashiwo, Chaetoceros curvisetus, Tetraselmis subcordiformis, S. costatum and Gymnodinium sp..…”
Section: Page 4 Of 14mentioning
confidence: 95%
“…Representing both single cells and an entire organism, the unicellular alga Chlamydomonas is a suitable model system to study cell death. It is an established model for elucidation of heavy metal tolerance, stress validation and physiological processes such as respiration, photosynthesis, cell propagation and nutrient uptake (Harris, 2001; Hanikenne, 2003; Hema et al, 2007; Deponte, 2008). Exposure of Chlamydomonas reinhardtii to UV has been shown to induce hallmarks of apoptotic‐like PCD such as the breakdown of DNA into oligonucleosomal fragments (DNA laddering) and occurrence of TUNEL (terminal deoxynucleotidyl transferase‐mediated dUTP nick end labelling)‐positive nuclei (Moharikar and D'Souza, 2006).…”
Section: Introductionmentioning
confidence: 99%